STRATEGI PENGEMBANGAN USAHA PRODUKSI TAHU LOLOR DI KECAMATAN MASBAGIK KABUPATEN LOMBOK TIMUR - Eko Supriastuti; Mutiara Mita Kasia; Farah Ainul Jamil (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2026)
Lolor tofu is a typical tofu product from Masbagik District, East Lombok Regency. Lolor tofu is made from soybeans which has a different texture from tofu in general. The texture of lolor tofu is relatively smooth and chewy with a shape like a cow's brain (lolor). The texture and shape of lolor tofu are characteristic so that it is very popular with consumers. However, producers have not been able to develop their business to a larger scale, marketing of lolor tofu is still small-scale or home-based. This is because producers do not yet know the strategy used to develop a lolor tofu business. This study aims to: Determine the internal and external factors of developing a lolor tofu production business in Masbagik District and formulate a strategy for developing a lolor tofu production business in Masbagik District. The method used in this study is a descriptive method. The unit of analysis of this study is the lolor tofu consumer. The number of respondents was determined by quota sampling of 10 respondents each in each selected hamlet so that the total number of respondents was 30 respondents. The determination of respondents was carried out using an accidental sampling approach, and analyzed using a SWOT analysis. he analysis results obtained several strategies, namely 1). Optimizing the supply of local raw materials with government support. 2). Utilizing the distinctive taste to attract healthy consumers to expand the tofu lolor market by promoting the product through digital platforms. 3). Business management training from related agencies on packaging design and branding, legality and distribution permits through online platforms. 4). Establishing partnerships with cooperatives or BUMDes for access to capital. 5). Optimizing the supply of local raw materials with government support. 6). Utilizing the distinctive taste to attract healthy consumers to expand the tofu lolor market by promoting the product through digital platforms. 7). Improving production quality to be able to compete by designing product labels according to BPOM/PIRT standards. 8). Diversifying products and marketing channels to strengthen appeal.